2000
DOI: 10.2355/isijinternational.40.1149
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Microstructure and Tensile Strength of Cold Rolled Pearlitic Steel Sheets

Abstract: The deformation microstructure produced by heavy cold rolling (from 70 % to 95 % reduction) of pearlitic structure with various amounts of rolling and the tensile strength of the cold rolled sheets were studied in the plain carbon steels with various carbon contents (0.6, 0.76, and 1.0 mass%C). The deformation microstructure was classified into the following three types; 1) Irregularly Bent Lamella (IBL): lamellae originally inclined with large angles to the rolling plane and irregularly bent after deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…The arrangement of lamellae is not uniform in cold-rolled pearlite. As was previously reported, 6) the cold-rolled pearlite structure can be classified into three types shown in the corresponding schematic illustrations; (A) irregularly bent lamellae (IBL) where alignment of q lamellae changes severely by deformation without fragmentation; (B) coarse lamellae with shear band (CLS) which consists of the area with coarse interlamellar spacing and shear bands inclined at about 30 degrees to RD; (C) fine lamellae (FL) where a and q lamellae are almost parallel to RD with fine interlamellar spacing. Figure 3 shows the variation of deformed structure with the rolling reduction.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…The arrangement of lamellae is not uniform in cold-rolled pearlite. As was previously reported, 6) the cold-rolled pearlite structure can be classified into three types shown in the corresponding schematic illustrations; (A) irregularly bent lamellae (IBL) where alignment of q lamellae changes severely by deformation without fragmentation; (B) coarse lamellae with shear band (CLS) which consists of the area with coarse interlamellar spacing and shear bands inclined at about 30 degrees to RD; (C) fine lamellae (FL) where a and q lamellae are almost parallel to RD with fine interlamellar spacing. Figure 3 shows the variation of deformed structure with the rolling reduction.…”
supporting
confidence: 72%
“…[3][4][5] The present authors studied the microstructure and mechanical property of cold-rolled pearlite. 6) Whereas similar changes in microstructure and property by cold rolling of pearlite as in cold drawing were observed, it was found that the cold-rolled structure of pearlite was surprisingly inhomogeneous. When heavily cold-rolled pearlite is annealed, the ultra-fine grained duplex structure with ferrite (a) and cementite (q) grain sizes less than 1 mm was easily obtained.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…For example the tensile strength of severely cold-rolled pearlitic UHCSs is 2500 MPa. 42 This is equivalent to a nano-hardness of 6.3 Gpa. 43 The result indicates that adiabatic shear, involving a temperature rise during deformation, is a requirement for ultrahigh strength.…”
Section: Nanohardness Of the Shear Bandmentioning
confidence: 99%
“…1) Pearlite, which consists of ferrite (a ) and lamellar cementite (q ), is one of the most important structures in steels. For the pearlitic structures, both reduction of interlamellar spacing of pearlite (ISP) and thinning of lamellar q occur through heavy cold rolling, 2,3) and the spheroidization of a lamellae can be quite accelerated during subsequent annealing, 4) leading to the formation of (a +q ) microduplex structures. [5][6][7] The refinement of q particles, which should result in the refinement of a grain size by pinning effects, is very important for strengthening the alloy with the (a +q ) microduplex structure.…”
Section: Introductionmentioning
confidence: 99%